Biological magnetic ion exchange resin on advanced treatment of synthetic wastewater. (March 2023) - Xu, Shanshan; Yan, Yunbao; Shuang, Chendong; Zhou, Qing; Ji, Rong; Li, Aimin
Graphical abstract: Highlights: Biological ion exchange employing magnetic resin was established (bio-MIEX). Bio-MIEX presented the best removal of DOC (84%) and ibuprofen (100%) after 50 d. The ATP amount of bio-MIEX was 1.48 µg/g and the protein amount was 2.11 mg/g. Bio-MIEX showed the highest microbial diversity, dominated by Aquitalea (14.9%). The superior performance of bio-MIEX was due to the presence of Fe3 O4 . Abstract: In this work, three biological ion exchange systems and one biological activated carbon (BAC) system were established by employing magnetic ion exchange resin (MIEX), non-magnetic resin (NIEX), polystyrenic resin (DIEX) and granular activated carbon as the biocarrier for advanced treatment of wastewater. Dissolved organic carbon (DOC) removal of four systems all stabilized at about 84% due to biodegradation. The start-up period of bio-MIEX (nearly 40 d) was greatly shorter than that of others (nearly 190 d). Ibuprofen removal was ascribed to adsorption in the initial stage, which subsequently changed to the effect of biodegradation. After the start-up period, ibuprofen removal was nearly 100% (bio-MIEX), 60% (bio-NIEX), 61% (bio-DIEX) and 89% (BAC). According to the surface observation, ATP and protein measurement and metagenomic analysis, the superior performance of bio-MIEX could be attributed to its highest biological activity resulted from the presence of Fe3 O4 rather than polymer matrix and surface roughness.